Assessing the mediating role of marketing capability in the relationship between TQM practices and innovation performance dynamic capabilities approach - Yusr, Maha Mohammed; Othman, Abdul Rahim; Mohd Mokhtar, Sany Sanuri (Centre for Promoting Ideas, 2012)
Achieving high innovation performance has been considered as the best way to compete, survive, and gain market share in the hyper competitive market. To do so, companies need to enhance and build its capabilities which represent the main antecedents of innovation performance. In response to the aforementioned issue, this study aims to investigate the effect of TQM as an effective organizational philosophy that enhances organizational performance and marketing capabilities, and in turn, innovation performance. To this end, a primary data is collected from the manufacturing companies in Malaysia. Then, data is analyzed through Partial Least Square PLS-SEM technique. The obtained results support all the formulated hypotheses.